2002
DOI: 10.1159/000067435
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Patients with Microsurgically Resected Brain Metastases

Abstract: Background: With the advent of new therapies for metastatic carcinoma to the brain, patterns of intracranial disease and factors influencing survival become important considerations when examining treatment options. This study was conducted at a single institution to determine prognostic factors for tumor response and patient survival after microsurgical resection of brain metastases. Patients and Methods: 187 consecutive patients who underwent microsurgical resection of brain metastases between July 1989 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Much of the research in therapeutics for brain tumours has focused on radiation therapy [17], chemotherapy [23] and surgery [16], or a combination of the above. We propose that a complementary future direction of brain tumour research is to harness the intrinsic defenses of the body against cancer and promote neurological recovery through exercise therapy after acute multi-modal treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the research in therapeutics for brain tumours has focused on radiation therapy [17], chemotherapy [23] and surgery [16], or a combination of the above. We propose that a complementary future direction of brain tumour research is to harness the intrinsic defenses of the body against cancer and promote neurological recovery through exercise therapy after acute multi-modal treatments.…”
Section: Discussionmentioning
confidence: 99%
“…It may be that neurosurgeons, neurologists and neuro-oncologists are either not aware of rehabilitation services or do not believe in the benefits of rehabilitation [6], although several studies have shown that patients with brain tumours do make significant functional gains following rehabilitation [7][8][9][10][11][12][13][14]. Another barrier to rehabilitation therapy in patients with brain tumours is that physiatrists (specialists in physical medicine and rehabilitation) may be uncomfortable providing such care for a progressive disease with poor prognosis since the life expectancy is a year or less for those with brain metastases [15][16][17] and glioblastoma multiforme (GBM) [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Elderly individuals comprise a major proportion of neurosurgical patients. [9][10][11][12] The number of elderly patients is likely to rise in the future as a result of: (i) increasing survival of cancer patients; (ii) improvements in the detection of brain metastases; and (iii) resistance of brain metastases to effective therapeutic agents because of the blood-brain barrier. 9,10,13,14 We performed a retrospective study of 309 patients with brain metastasis using univariate and multivariate survival analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the improvement of survival, this leads to an improvement of symptoms in a large percentage of patients [6]. Image-guided surgery has facilitated the surgery by means of minimally invasive targeting and resection.…”
Section: Current Surgical Techniques and Goal Of Surgerymentioning
confidence: 99%